The influence of English-speaking environment on young learners: The rationale - Thoriq Aulia; Saraswati, Girindra Putri Dewi (ELT Forum: Journal of English Language Teaching, 2025)
The significance of English-speaking settings in aiding young learners oral language growth has received worldwide recognition, particularly in bilingual education situations. Even with the increasing interest, there is still a shortage of thorough research that combines theoretical frameworks and up-to-date empirical studies on the subject, especially within the Indonesian context. This research intends to examine the impact of English-speaking settings on the speaking skills of young learners using a library research method. In accordance with Creswell’s (2014) principles for qualitative research, this study methodically examines and integrates academic literature, emphasizing peer-reviewed publications from 2020 to 2025. The results highlight five main areas influenced by English-speaking settings: heightened motivation and confidence, decreased speaking anxiety, enhancement of social interactions, advancement in language skills (pronunciation, fluency, grammar), and the use of relevant, context-oriented learning techniques. These findings are consistent with Krashen’s Input and Affective Filter Hypotheses, Vygotsky’s Sociocultural Theory, and Long’s Interaction Hypothesis. The research finds that engaging and nurturing English-speaking settings are crucial for promoting successful language growth in early childhood. It also emphasizes educational implications, including the necessity for emotionally supportive learning environments, collaborative learning among peers, and contextually relevant teaching. This study establishes a theoretical basis for educators and policymakers to create improved bilingual education programs and suggests guidance for upcoming empirical investigations.